Structure of Algal Community and Ecological Features of Dominant Species in the Sudochye Water Bodies - Eshmurodova, Nargiza Sharofovna (American Journal of Biodiversity, 2025)
This study presents the results of a comprehensive investigation of algocenoses in the Sudochye lake system, including ecological monitoring, hydrobiont biodiversity assessment, and analysis of community structure under conditions of elevated mineralization. Emphasis was placed on the taxonomic composition, ecological traits, and distribution patterns of algae, along with the ecological valence of dominant species. Long-term climatic data were also analyzed, revealing a gradual linear increase in mean annual air temperature and peak precipitation in March, June, and October. From 1979 to 2024, average annual precipitation was 113.2 mm, with anomalies up to 24.1 mm. These findings enhance understanding of algal dynamics and the ecological status of aquatic ecosystems in arid, saline environments.